KARAKTERISTIK SUPERVISI AKADEMIK HUMANIS: Transformasi Pendampingan Guru Menuju Pembelajaran Bermutu - Gazali, Moh Salim; Atnawi, Atnawi (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2025)
Academic supervision is one of the strategic instruments in education management to improve teachers' professional competence and the quality of learning in schools. In contrast to conventional supervisory patterns that are authoritarian, academic supervision emphasizes a democratic, collaborative, and constructive approach that positions teachers as partners in the coaching process. This study aims to outline the characteristics of effective academic supervision and its relevance to improving teacher performance in madrasas. The research method used is library research by examining various sources of literature, educational regulations, and relevant previous research results. The results of the study show that effective academic supervision has main characteristics, including based on a scientific approach, based on humanist relationships, oriented towards teacher professional development, and constructive and sustainable. In addition, the clinical supervision model is one of the prominent forms of academic supervision, with stages of planning, observation, and feedback carried out dialogically. The implementation of these characteristics has an impact on increasing teachers' pedagogic competence, optimizing learning management, and forming a quality culture in the school environment. Thus, the implementation of planned, collaborative, and continuous academic supervision is the key to developing teacher professionalism and improving the quality of education in madrasas.